2019
DOI: 10.1016/j.jnucmat.2019.05.034
|View full text |Cite
|
Sign up to set email alerts
|

Heavy ion irradiation damage in Zr2AlC MAX phase

Abstract: Zr2AlC MAX phase-based ceramic material with 33 wt.% ZrC has been irradiated with 22 MeV Au 7+ ions between room temperature and 600 o C, achieving a maximum nominal midrange dose of 3.5 displacements per atom. The response of the material to irradiation has been studied using scanning electron microscopy, transmission electron microscopy and X-ray diffraction. Under room temperature irradiation, the ions caused a partial amorphisation of the MAX phase. At high temperatures, irradiated Zr2AlC remained crystall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Cracks parallel to the (0001) basal planes of the MAX phase appear on some grains in Fig. 4; these are characteristic of MAX phase materials; they are also observed in pristine Zr 2 AlC MAX phase [28] and the pristine Zr 3 AlC 2 MAX phase produced by Bowden et al for their irradiation work [29] . Post-irradiation examination of all the irradiated materials revealed no topographical discrepancies relative to the pristine sample, indicating that the ion irradiation did not alter the topography of the phases noticeably at a micrometre level.…”
Section: Microstructurementioning
confidence: 77%
See 2 more Smart Citations
“…Cracks parallel to the (0001) basal planes of the MAX phase appear on some grains in Fig. 4; these are characteristic of MAX phase materials; they are also observed in pristine Zr 2 AlC MAX phase [28] and the pristine Zr 3 AlC 2 MAX phase produced by Bowden et al for their irradiation work [29] . Post-irradiation examination of all the irradiated materials revealed no topographical discrepancies relative to the pristine sample, indicating that the ion irradiation did not alter the topography of the phases noticeably at a micrometre level.…”
Section: Microstructurementioning
confidence: 77%
“…Prior to the work reported here, there have been two studies, one on Zr 2 AlC [28] and one on Zr 3 AlC 2 and (Zr 0.5 Ti 0.5 ) 3 AlC 2 [29]. In the first of these two studies, Zr 2 AlC irradiated with Au 7+ ions was shown to develop significant lattice disorder and partial amorphisation upon irradiation to 3.5 dpa at RT conditions, whereas at 300 °C and 600 °C it exhibited relatively good irradiation resistance [28]. The second study used protons as their source of radiation, with irradiation temperatures of 350 °C and 575 °C [28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zr is neutron transparent because its thermal neutron absorption cross -section is relatively tiny (Zr atoms have a small cross section for thermal neutrons), which can help nuclear reactors maintain a high neutron economy. As a result, it is routinely utilized in today's nuclear reactors [54]. Aside from economic reasons, Next-generation (Gen-III+) light water reactors (LWRs) require fuel cladding materials that can survive difficult operating circumstances such high mechanical and thermal loads, large neutron irradiation doses, and intensely oxid izing or corrosive environments [39].…”
Section: Future Perspective With Applications Of Zr 2 Ac Max Phasementioning
confidence: 99%
“…In recent years, there has been a search for different applications for the use of this family of materials. Their use as heat exchangers [7] or catalytic devices using porous Ti 3 SiC 2 and Ti 2 AlC [8], thermal barriers using Cr 2 AlC [9] or as fuel cladding material in nuclear reactors using Zr 2 AlC [10] are some of the possible applications of these materials.…”
Section: Introductionmentioning
confidence: 99%